Discourses and policies on educational quality in Argentina 1990-2010 - Gorostiaga, Jorge Manuel (2012)
This article analyses the relationships between different notions of education quality and policies on primary and secondary schools implemented in Argentina during the last two decades. The authors focus on three moments: (1) the emergence of the discussion about quality (at the end of the 1980s) in Latin America and in Argentina; (2) the enactment and implementation of the Federal Law of Education (1993); and (3) the enactment of the Law of National Education (2006), along with the implementation of some key policies.